Accurate Frequency Tracking Using Morphological Predication of Clarke Components - et al., Srihari Mandava (International Journal of Advanced Science and Technology, 2019)
This article gives an algorithm for the calculation of frequency using the morphological prediction of Clarke components (MPCC) given by αβ-transformation. It uses four operators’ dilation, erosion, opening and closing for different types of frequency varying conditions. It also presents the comparison of two algorithms, MPCC and PLL, in real time signal by creating a grid in MATLAB Simulink. The algorithms were tested with two types of faults, symmetrical and unsymmetrical faults, at the same time the later algorithms will be compared with two types of loads such as linear and non-linear loads. These demonstrations show us, how accurate the MPCC is when compared to PLL in estimating frequency.